Description And Level Of Degradation Of Sea Sea Based Ecosystems In The Coastal Area Of Uwedikan Village, East Luwuk District, Banggai District - Yantu, Oktavianingsi A. H.; Utina, Ramli; Husain, Ilyas (Jurnal Media Akuakultur Indonesia, 2023)
The seagrass ecosystem is an ecosystem that is very important to support the sustainability of the biota that take shelter in it. The seagrass ecosystem is known as one of the areas that is vulnerable to damage. Various human activities, such as fishing and industrial activities can trigger this damage. This study aims to provide information regarding the description and level of degradation of the seagrass meadow ecosystem in Uwedikan Village. The method used is random sampling method. The results showed that there were 5 species of seagrass found, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea Serullata, Cymodocea rotundata and Halophila ovalis. Seagrass cover averaged 40.60% at Tanjung Balean and 33.1% at the Tambatan Perahu. This is included in the moderate/less rich category. The highest seagrass cover was for Thalassia hemprichii with a total of 2,169 individuals at Tanjung Balean and 1,453 at the Boat Mooring. The relationship of water parameters, namely temperature, degree of acidity (pH) and brightness greatly affect the growth of seagrass ecosystems. In particular, the temperature at the two locations obtained different values, namely 29--30.5Â°C at Tanjung Balean and 30--35.3Â°C at the Tambatan Perahu.